ANALISIS PENGARUH FUNGSI INTERMEDIASI PERBANKAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA TAHUN 2008 - 2011 - . Anjarwati (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2013)
This study aims to analyze the development of intermediation to economic growth in Indonesia and a significant test whether or not the effect of intermediation on economic growth. From the test results obtained by the coefficient of determination (R2) for multiple linear regression models for 0.916. It means that the independent variables can explain the variation in the dependent variable 91.6% together, then variable t can be seen that variable Interest Rate Loans and lending have a significant effect on economic growth, It is proved that t-count > t-table. Lending to the variable (X1) 7,944 t > t table 2.026, and for variable Interest Rate Loans (X2) 4.521 t-count > t table 2.026. From the analysis has been conducted simultaneously indicates that those independent variables have a significant effect on economic growth, with simultaneous F test results are calculated F value > F 204.012> 3.25. it means that Ho is rejected.